PENGARUH PEMBERIAN PAKAN DARI SUMBER NABATI DAN HEWANI TERHADAP BERBAGAI ASPEK FISIOLOGI IKAN GURAMI {Osphronemus gouramy L.) [The Effect of Plant and Animal Food on Various Physiological Aspects of Giant Gouramy (Osphronemus gouramy L.)] - Erwin Nofyan (Jurnal Iktiologi Indonesia, 2005)
The research on the effect of plant and animal food on various physiological aspect of gouramy fish (Osphronemus gouramy L.) was conducted from January to July 2003. The design used completely randomized design. The treatments were taro leaf, water hyacinth leaf powder, fish, and Tubifex powder. Parameter of experiment was food intake efficiency, growth rate, and specific growth rale. The experiment on food intake efficiency was conducted for one day where as the growth rate and specific growth rate lor five months (150 days). The research showed that the food intake efficiency, growth rate and specific growth rate depended on the specific food given. The highest food intake efficiency of fish was obtained in the fish powder treatment (45.95 ± 2.59%) and the lowest in the water hyacinth leaf powder treatment (22.64 ± 2.70%). Treatment with fish powder increased the growth rate of 0.68 ± 0.08 g/individual/day, and the lowest growth rate in the water hyacinth treatment (0.13 ± 0.05 g/individual/day) during 150 days of observation. The highest specific growth rate of gouramy was obtained in the fish powder treatment (82.50 ± 1.23%) and the lowest in the water hyacinth leaf powder treatment (22.3 ± 0.58%), during 150 days of observation. The highest protein content founded in the fish powder was 66.53% and the lowest protein content founded in the water hyacinth leaf powder was I 7.20%